2017
DOI: 10.1080/08039488.2017.1340517
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the neutrophil-lymphocyte, platelet-lymphocyte and monocyte-lymphocyte ratios in schizophrenia and bipolar disorder patients – a retrospective file review

Abstract: Neutrophil-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR) and monocyte-lymphocyte ratio (MLR) have recently been used as indicators of inflammation. Higher MLR and PLR values have been determined in the euthymic and manic periods in patients with bipolar disorder compared to a control group. High NLR values were determined in the only study investigating this ratio in schizophrenia patients. The purpose of this study was to compare NLR, PLR and MLR values and complete blood count elements in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
65
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(85 citation statements)
references
References 18 publications
7
65
5
1
Order By: Relevance
“…[31][32][33] Immunemediated alterations in serotoninergic and glutamatergic systems may result in mood and cognitive symptoms while inflammation-induced modifications of dopaminergic Open access systems may result in motivational deficits found across different psychiatric disorders. 34 In contrast to previous reports, [15][16][17] we did not find NLR to differ between bipolar affective disorder and schizophrenia, between bipolar affective disorder or depression, or between depression and AD after correcting for covariates. This contradiction in findings may be attributed to the larger sample size in our study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…[31][32][33] Immunemediated alterations in serotoninergic and glutamatergic systems may result in mood and cognitive symptoms while inflammation-induced modifications of dopaminergic Open access systems may result in motivational deficits found across different psychiatric disorders. 34 In contrast to previous reports, [15][16][17] we did not find NLR to differ between bipolar affective disorder and schizophrenia, between bipolar affective disorder or depression, or between depression and AD after correcting for covariates. This contradiction in findings may be attributed to the larger sample size in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…5 True transdiagnostic studies are rare with only three studies to date comparing NLR between psychiatric diagnoses. [15][16][17] Of the NLR studies comparing different psychiatric diagnoses, Ozdin et al reported that patients with schizophrenia, experiencing a psychotic episode, had higher NLR than patients with manic-phase BD, suggesting that there are detectable differences in NLR across diagnosis and symptomatology. 15 Mazza et al found that patients with manic-phase BD had higher NLR than patients with major depressive disorder (MDD).…”
mentioning
confidence: 99%
“…However, less is known on the role of MPO in individuals without symptomatic CVD, but epidemiologic studies demonstrate that MPO may predict future risk of coronary artery disease ( 50 ). Furthermore, elevated neutrophil counts have been reported in BD and SCZ ( 51 53 ) and based on the increased MPO levels observed in our study, it is tempting to speculate that abnormalities in neutrophil activation could represent an early event in the progression of CVD in patients with psychotic disorders. The stronger association with the TC/HDL compared to the TG/HDL, could suggest that the enhanced MPO is more directly linked to atherogenesis and not only a marker of this process.…”
Section: Discussionsupporting
confidence: 57%
“…Neutrophil-lymphocyte ratio (NLR) have been used as an indicator of inflammation. An elevation of NLR and neutrophils, and lower levels of lymphocytes were found in patients with SZ 44,45 . NLR is a strong predictor of systemic inflammation; NLR high values may be involved in the pathophysiology of SZ (inflammatory hypothesis), and also may be correlated with cognitive impairment 46,47 .…”
Section: Resultsmentioning
confidence: 93%